2010
DOI: 10.1590/s0482-50042010000600003
|View full text |Cite
|
Sign up to set email alerts
|

Interação entre qualidade do meio ambiente, estresse e a variação do gene APOE na determinação da suscetibilidade à fibromialgia

Abstract: Introduction: Fibromyalgia is a multifactorial disease, of which etiology is based on interaction between genetic susceptibility and environment. However, few studies attempted to identify the risk factors. Objective: To investigate the genetic influence and its interaction with environmental quality and stress, as possible risk factors for fibromyalgia development. Patients and Methods: This cross-sectional study investigated two groups of women, of which 47 had a clinical diagnosis of fibromyalgia, and 41 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…35 When investigating the relationship between pain and stress in patients with FM and healthy individuals, Ferreira et al 42 have found no signifi cant difference in the number of stressing events between both groups, attributing their result to the way patients cope with stress, and not only to the intensity of the events experienced. Differently, Becker et al 43 have reported a relationship between high levels of stress and that syndrome, in addition to the existence of an interaction between the apolipoprotein E gene polymorphism and stress in FM.…”
Section: Figurementioning
confidence: 93%
“…35 When investigating the relationship between pain and stress in patients with FM and healthy individuals, Ferreira et al 42 have found no signifi cant difference in the number of stressing events between both groups, attributing their result to the way patients cope with stress, and not only to the intensity of the events experienced. Differently, Becker et al 43 have reported a relationship between high levels of stress and that syndrome, in addition to the existence of an interaction between the apolipoprotein E gene polymorphism and stress in FM.…”
Section: Figurementioning
confidence: 93%
“…Os 17 artigos que usaram como instrumento o WHOQOL-100 tiveram como público alvo profissionais da saúde (5 artigos); portadores de dor e/ou doença crônica (seis artigos, sendo dor crônica, 2; portadores de lúpus eritematoso sistêmico, 2; deficientes visuais, 1 e mulheres mastectomizadas, 1 artigo); idosos (2 artigos), cuidadores ( 1artigo). Dois artigos, embora avaliando uma condição crônica, a fibromialgia, foram considerados em separado, pois avaliaram um domínio específico -o ambientecomo um fator de risco para o desenvolvimento da doença, em associação a fatores genéticos (BECKER et al, 2010e MERGENER et al, 2011. Ressalte-se o refinamento estatístico de todos os artigos consultados, com amostragem adequada, estatística analítica e, em seis artigos, sendo cinco os de avaliação de condições crônicas, grupo controle.…”
Section: Resultsunclassified
“…Other studies of patients with FMS have shown that pain is the worst aspect related to the low quality of life reported by patients. [25][26][27] Such studies have aimed only at assessing how much the disease and its treatment infl uence the quality of life of patients, associating the results with clinical aspects or comparing them with healthy individuals or patients with other diseases. All these approaches have concluded that the use of the WHOQOL-100 questionnaire as an instrument for clinical follow-up is very interesting to assess symptoms.…”
Section: Resultsmentioning
confidence: 99%